Single pole‐to‐ground fault location method for MMC‐HVDC system using active pulse. Issue 2 (16th October 2017) - Bi, Tianshu; Wang, Shuai; Jia, Ke
Abstract : Modular multilevel converter HVDC (MMC‐HVDC) systems have been commissioned in China, America and Europe. With the demand of long‐distance and large‐capacity power transmission, the MMC‐HVDC systems using overhead lines get more attention. When a single pole‐to‐ground permanent fault occurs, the fault current is very small, therefore if the fault location is determined, the fault can be cleared and the HVDC system can revert to normal operation without interruption. MMC‐HVDC can quickly control the work state of sub‐modules (SMs), therefore, it is possible to generate travelling wave pulses propagating to the line by controlling SM, without the need of additional equipment. So in this study, a fault location method for MMC‐HVDC using active pulse is proposed. Meanwhile dichotomising recursion singular value decomposition is used to detect the arrival time of active pulse. The proposed method does not require additional equipment and the method is not influenced by transition resistance. And fault location can be repeated since the pulse can be sent repeatedly. Computer simulations are performed and the results show that the proposed method can locate the grounding point of MMC‐HVDC reliably and with increased accuracy relative to existing methods.